2002
DOI: 10.1215/03616878-27-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Partnerships for Community Health Improvement: Tracking the Footprints

Abstract: Private-public partnerships are increasingly seen as an important mechanism for improving community health. Despite their popularity, traditional evaluations of these efforts have produced negative or mixed results. This is often attributed to weak interventions or an insufficient period of time to observe an impact. This study examines two additional possibilities--the need for a well-articulated shared vision and the governance and management capabilities of the partnership itself. We conducted a midstream p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
188
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 180 publications
(198 citation statements)
references
References 26 publications
7
188
1
1
Order By: Relevance
“…Additionally, where grant makers require reporting of evidence of intermediate outcomes, this has the potential to promote success in the longer term. 51,52,65 These findings are linked to what Shortell et al 52 describe as 'recognising life cycles', suggesting that, where members are familiar with the stages of development of the collaborating partnerships, they are more able to address issues and seek solutions.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Additionally, where grant makers require reporting of evidence of intermediate outcomes, this has the potential to promote success in the longer term. 51,52,65 These findings are linked to what Shortell et al 52 describe as 'recognising life cycles', suggesting that, where members are familiar with the stages of development of the collaborating partnerships, they are more able to address issues and seek solutions.…”
Section: Resultsmentioning
confidence: 77%
“…50 Olson et al 50 found that the success of the collaboration is promoted where personal and emotional connections to the subject area are made by those involved and thereby provide the motivation to make changes and take action. Collaborations involving initiatives which are linked in such a way that they appear to be related to each other are more successful, according to Shortell et al, 52 who suggest that this relates to the synergy between initiatives, allowing partnerships to achieve their intended objectives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations